2012
DOI: 10.1002/etc.1951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental lead contamination on cattle in a lead/zinc mining area: Changes in cattle immune systems on exposure to lead in vivo and in vitro

Abstract: The Republic of Zambia is rich in mineral resources, such as zinc (Zn) and lead (Pb), and mining is a key industry in Zambia. A previous study of Pb pollution in Kabwe, one of the main mining areas, found that soil was contaminated with high levels of toxic metals over a substantial area. In the present study, the authors focus on toxic metal pollution in cattle, one of the most important domestic animals in Zambia. Blood samples from cattle in Kabwe and a control area (Lusaka) were tested for toxic metal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Despite extensive Pb pollution in Kabwe, comprehensive studies of Pb exposure and poisoning in children in the vicinity of the mine are rare. In animal studies however, high concentrations of Pb were reported in wild rats (Nakayama et al 2011;Nakayama et al 2013) as well as blood and edible organs of cattle (Yabe et al 2011;Ikenaka et al 2012) and chickens (Yabe et al 2013) reared in the vicinity of the mine in Kabwe. Therefore, the objectives of the current study were to investigate BLLs in children under the age of 7 years in townships around the Pb-Zn mine in Kabwe and to identify children with BLLs that require medical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive Pb pollution in Kabwe, comprehensive studies of Pb exposure and poisoning in children in the vicinity of the mine are rare. In animal studies however, high concentrations of Pb were reported in wild rats (Nakayama et al 2011;Nakayama et al 2013) as well as blood and edible organs of cattle (Yabe et al 2011;Ikenaka et al 2012) and chickens (Yabe et al 2013) reared in the vicinity of the mine in Kabwe. Therefore, the objectives of the current study were to investigate BLLs in children under the age of 7 years in townships around the Pb-Zn mine in Kabwe and to identify children with BLLs that require medical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Pb exists in the environment in a vapor or solid form, and is a ubiquitous, highly toxic, nonessential element. Studies from our laboratory and those of other groups recorded higher levels of Pb than the established maximum permissible limits in different human food items of animal and plant origin, including meat, edible offal, fish, poultry, and crops (Burger and others ; Yabe and others ; Ikenaka and others ; Morshdy and others ). Heavy metals, particularly Pb, are characterized by their persistent occurrence and accumulation (Korashy and El‐Kadi ; ATSDR ).…”
Section: Introductionmentioning
confidence: 47%
“…Heme biosynthesis does not decrease until the activity of ALAD is inhibited by 80 to 90%, which occurs at a much higher PbB concentration of about 550 µg/L. Consistently, it has been shown that hemoglobin levels do not begin to decrease until PbB levels are 500 µg/L in adults (Ikenaka et al, 2012; Patrick, 2006). In the present study, the mean hemoglobin levels in both examined groups were within the normal ranges and did not differ significantly.…”
Section: Discussionmentioning
confidence: 85%
“…These results may be caused by lead’s influence on the function of the immune system. It has been shown that lead may cause an imbalance between the Th1 and Th2 type of immunological response and increase levels of the proinflammatory cytokines such as interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α (Ikenaka et al, 2012; Jorissen et al, 2013; Shen et al, 2001). This increase may be due to lead-induced activation of NF-κB, which is one of the principal inducible transcription factors.…”
Section: Discussionmentioning
confidence: 99%